Skazka o t͡sare Saltane, o syne ego slavnom i moguchem bogatyre kni͡aze Gvidone Saltanoviche i o prekrasnoĭ t͡sarevne Lebedi - Pushkin, Aleksandr Sergeevich, 1799-1837 (Shedevry knizhnoĭ illi͡ustrat͡sii-- deti͡am, 2010)
Pushkin's poetic retelling of the Russian folk-tale which tells how Prince Gvidon saves his mother and himself from their enemies and gains a kingdom and a bride.